Working posture and its predictors in hospital operating room nurses - Abdollahzade, Farahnaz; Mohammadi, Fariba; Dianat, Iman; Asghari, Elnaz; Asghari-Jafarabadi, Mohammad; Sokhanvar, Zahra (Health promotion perspectives, 2016)
This study was conducted to evaluate working posture of operating room nurses and its relationship with demographic and job details of this group. This cross-sectional study was conducted among 147 operating room nurses in Tabriz, Iran using a questionnaire and the Rapid Entire Body Assessment (REBA) checklist. The data were analyzed with SPSS.16 using t test, Pearson correlation coefficient and analysis of variance (ANOVA) tests for univariate analysis and the linear regression test for multivariate analysis. The mean (SD) of REBA score was 7.7 (1.9), which means a high risk level and highlights an urgent need to change the working postures of the studied nurses. There was significant relationship between working posture and age (P = 0.003), gender (P = 0.003), regular daily exercise (P = 0.048), work experience (P = 0.003), number of shifts per month (P = 0.006) and type of operating rooms (P < 0.001) in univariate analyses. Gender and type of operating room were the predictors of working posture of nurses in multivariate analysis. The findings highlight the need for ergonomic interventions and educational programs to improve working posture of this study population, which can consequently lead to promotion of health and well-being of this group.